2016
DOI: 10.1371/journal.pcbi.1004893
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Residue Scan Simulations Systematically Reveal Residue Entropic Roles in Protein Allostery

Abstract: Intra-protein information is transmitted over distances via allosteric processes. This ubiquitous protein process allows for protein function changes due to ligand binding events. Understanding protein allostery is essential to understanding protein functions. In this study, allostery in the second PDZ domain (PDZ2) in the human PTP1E protein is examined as model system to advance a recently developed rigid residue scan method combining with configurational entropy calculation and principal component analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 89 publications
2
49
0
Order By: Relevance
“…In addition, 30 ns trajectory was carried out for each RRS simulation to be consistent with unperturbed simulations. Our previous study also support that the 30 ns trajectories are sufficient to probe protein allosteric mechanisms34.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, 30 ns trajectory was carried out for each RRS simulation to be consistent with unperturbed simulations. Our previous study also support that the 30 ns trajectories are sufficient to probe protein allosteric mechanisms34.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, a few computational and experimental reports suggested that La Châtelier's principle may be behind dynamic allostery. Using a rigid residue scan molecular dynamics simulation-based method, Kalescky et al (20,21) reported that decreasing local entropy by increasing individual residue rigidity of PDZ domain proteins often leads to increasing global configurational entropy. Recently, biophysical experiments performed by Law et al (22) revealed that the volume of PDZ3 domain protein is coupled with local internal motion, following La Châtelier's principle.…”
mentioning
confidence: 99%
“…To demonstrate our SVD‐based correlation analysis of allosteric proteins, we apply the method to the PDZ2 domain in hPTP1E, a model system in allosteric studies containing 94 residues (PDB ID 3LNY). The conformation ensemble was sampled by MD simulations of a coarse‐grained Gō‐like model (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis reveals that significant inter‐residue and inter‐domain couplings as well as the allosteric response can be inferred from correlated atomic fluctuations. Conventionally, the cross‐correlations of atoms or residues are measured by the DP form of the correlation coefficient, defined as CijDP=ΔboldriΔboldrjΔboldri212Δboldrj212, where Δ r i and Δ r j are the displacements of residues (atoms) i and j from their average positions, respectively. Here, the superscript “DP” distinguishes the DP correlation coefficient from the proposed correlation coefficient (defined below).…”
Section: Introductionmentioning
confidence: 99%